Challenging the belief in simple solutions: The need for epistemic practices in professional work. Issue 1 (16th August 2020) - Nerland, Monika; Hasu, Mervi
Abstract: Context: As a contribution to the State of the Science issue on 'The problem with solutions', this paper discusses how technology‐mediated and assumedly simple and straightforward solutions to professional problems in fact require extensive work from professionals in order that generalised tools and procedures can be made sense of, adapted and employed in local practice. Theoretical perspective: The authors introduce a perspective on epistemic practices in professional work and learning in order to conceptualise and discuss the diversity of the knowledge‐related actions required to perform professional services. They discuss how the growing numbers and diversity of knowledge‐generating actors who aspire to inform professional practice create 'multi‐charged' work settings, imbued with multiple objectives and purposes. This development presents new epistemic challenges to professionals, which require extended capacities for knowledge work. Summary: The authors give examples from empirical studies conducted in Nordic health care settings, which relate to nurses' engagement with repositories of clinical procedures and to the development of new medical technologies for clinical use. They show how work performance in both cases depends on a range of epistemic practices (ie, collective ways of exploring, assessing, critically examining and justifying knowledge claims), which are necessary if the general tools and technologies are to be put to work in the local environment. This forms a core dynamic in practitioners' work‐based learning as it moves between what is known and what remains to be explored or improved. Conclusions: The paper argues that the widespread belief in simple or versatile solutions is challenged by research that reveals the diversity of the knowledge practices needed to perform professional services. The paper suggests that professional communities might pay more attention to epistemic practices as means to handle complexity. It raises intriguing questions and discusses implications for medical education. Abstract : Research reveals that a diversity of knowledge practices are needed to perform professional services. Nerland and Hasu suggest paying more attention to that as a means to handle complexity.